Discourse analysis on teacher-students interaction pattern of English teaching learning process in vocational high school - Bayu Jati Raharja (Journal of English Language and Pedagogy, 2020)
The objectives of this research are to (1) describe patterns of teacher-student interaction of English Teaching-Learning process in the Tenth Grade of SMK Negeri 1 Saptosari Gunungkidul, and (2) reveal the interactional features used by the teacher related to the pedagogic goals during the teaching-learning process. This research belongs to discourse analysis which aims at describing conversation and interaction of teacher-students during English teaching-learning process in the tenth grade of SMK Negeri 1 Saptosari Gunungkidul. The data were collected through observation and backed up with reading and were analyzed using the theory of the IRF exchange structure and the SETT Framework (Walsh, 2006). The result showed that there were 20 patterns of interaction of 21 exchange structures used in 7 types of transaction. The transactions were opening/greeting session, introduction, warm-up/re-checking session, explaining session, instruction session, practising session, closing/note-taking session. Some interactional features used by the teacher were found in the classroom interaction. There were 10 types of interactional features that were used by the teacher with the total number 115. The using of display question 47, confirmation checks 17, predominant of IRF was 12, use of scaffolding 11, form-focused feedback 9, clarification request 7, teacher turn by giving instructions 4, teacher turn by giving explanations 3, corrective repair 3, use of transactional marker 2. It revealed that the use of display questions was the most commonly used by the teacher in this classroom interaction. From the classroom interaction, it can be concluded that the teacher tended to pose display questions which prevented the students to express their elaborate ideas. The teacher also gave few scaffolding in her teaching and it hindered the students’ fluency. However, it might be effective for vocabulary learning through the exercise discussion.